Prevalence patterns of overweight and obesity in the world: An age-period-cohort analysis - Ali Kabir; Arman Karimi Behnagh (PLoS ONE, 2025)
Purpose This study aimed to evaluate the trends of obesity and overweight among adolescents using the age-period-cohort (APC) analysis. Methods Data for this study was provided by Institute for Health Metrics and Evaluation. Our data represents the cumulative prevalence trend of obesity and overweight in 195 countries between 1980 and 2015 in 5-year intervals. The age intervals were also considered to be 5 years. Besides, a subgroup analysis based on sex and socio-demographic-index subgroups were performed. To perform APC analysis, R program software was used. Results We observed an increasing trend in both obesity and overweight throughout the study period, with the trend accelerating in more recent periods. Among the fitted models, we concluded that the APC model best fit the current data. The trend for both outcomes was similar. Among the three parameters, age showed an inverted U-shaped effect on the trend of both outcomes in all subgroups. However, the effect of period and cohort differed in our subgroup analysis. Conclusion Overall, this study shows that obesity and overweight are on the rise. Both phenomena were influenced by the age effect in a similar pattern. However, the period and cohort effects showed variation in our subgroup analyses based on sex and SDI subgroups, suggesting the need for country-level studies to better understand the possible impact of these two factors on the prevalence of obesity and overweight.